Requalification of urban rivers in the context of renaturalization, revitalization and recovery - Silva, Juliana Caroline de Alencar da (2020)
The requalification of watercourses, mainly in urban areas, is a major challenge for the maintenance and resumption of the valuable ecosystem services provided by these areas, helping to increase the population's quality of life. Interventions in watercourses can be classified in different ways, depending on the degree of performance on each of the fronts involved in the process and the context in which the watercourse is inserted. In this study, a review of the existing literature on the subject was carried out in order to find which definition used for each type of requalification of water courses, and the predominant use of 3 terms was obtained: Restoration, Revitalization and Recovery. Restoration is dedicated to the return of the system to natural conditions, or to pre-development conditions. Already revitalization is dedicated to the creation of a new condition of balance, different from the natural condition, for the system so that it can support different types of urban uses. Finally, the recovery is dedicated to the reestablishment of the sanitary conditions of the system, which can be seen as an intermediate stage of revitalization and restoration. In view of the demands existing in each of the three techniques, this study carries out a critical analysis of the applicability of each of them to the Brazilian case.